Desarrollo de un ensayo de flujo lateral para la detección de ADN de Chlamydophila pneumoniae (2017)
"The current methods used for detection of C. pneumoniae include cell culture, serological tests and molecular techniques. DNA amplification by PCR has been used successfully in the diagnosis of C. pneumoniae infection because of its high sensitivity, specificity and simplicity. However, its use is restricted due in part to the need for costly equipment and relatively long times for the detection of reaction products. The present study reports the development of a method for detection of C. pneumoniae based on gold nanoparticles and DNA probes. The system presented here integrates DNA amplification by PCR and a lateral flow assay, which proved to be useful in the colorimetric detection of DNA amplicons of C. pneumoniae, in a time of about 35 min after amplification of DNA." -- Tomado del Formato de Documento de Grado.